WEB MOBILE PENGELOLAAN BARANG RAMPASAN DI KEJAKSAAN NEGERI REMBANG (Information Technology and Telematics, 2016)
determine the feasibility or determining the price of basic goods that the auction will be left to experts. Within the rules of the auction the spoils, the auction was to be completed within a period of four (4) months System development methods in this study is SDLC (System Development Life Cycle). Peracangan systems using UML and implementation of systems using PHP and MySQL. Results of this research is the creation of mobile web management booty in Rembang District Attorney State Attorney can facilitate Rembang in managing swag page where participants were made in the form of mobile web admin page while made in the form of web Keywords – Mobile Web, Auction, UML, PHP, MySQL